The status and hotspot analysis of research on extracellular vesicles and osteoarthritis: a bibliometric analysis - Zhang, Wen Hao; Xiang, Wen Yuan; Yi, Lin; Fang, Rui (Frontiers in Pharmacology, 2025)
BackgroundDegenerative joint disease, known as osteoarthritis (OA), is characterized by pain, swelling, and decreased mobility. The illness has a major negative influence on patients’ quality of life and is common around the world, especially among older people. Nevertheless, there are insufficient possibilities for early diagnosis and therapy. Extracellular vesicles, or EVs, control the immune response, tissue healing, and cellular communication.MethodsThis work offers a bibliometric representation of the areas of focus and correlations between extracellular vesicles and osteoarthritis. We searched for osteoarthritis and extracellular vesicles in publications in the Web of Science Core Collection (WoSCC) database. Bibliometrics, an R package, CiteSpace 6.1. R2, and VOSviewer 1.6.17 were used to perform bibliometric analyses of concentration fields, trends, and relevant factors.Results944 papers from 59 nations were published; the countries that contributed the most to the field were China, the USA, and Italy. Professors Laura and Enrico are the top contributors. Sichuan University, Istituto Ortopedico Galeazzi, and Shanghai Jiao Tong University are the top three universities. The International Journal of Molecular Sciences is an excellent publication. Exosome, expression, knee osteoarthritis, extracellular vesicle, mesenchymal stem cell, osteoarthritis, and inflammation are the most often occurring keywords.ConclusionThese results suggest areas of interest and focus for future research on EVs and OA. This trend suggests that the volume of literature on OA and EVs will continue to rise, with more research being published in the future. This study helps scholars understand current research hotspots in the field and may inspire future research.